OPTIMALISASI PENGAWASAN DAN PEMBINAAN HAKIM MENUJU KEKUASAAN KEHAKIMAN YANG BERINTEGRITAS DAN BERMARTABAT - Andi Hakim Lubis; Junaidi Lubis; Said Rizal (Ilmu Hukum Prima (IHP), 2022)
In carrying out its duties and functions as a mouthpiece of justice, it is necessary to carry out the function of monitoring and fostering judges optimally. So that every decision that has been determined by the judge maintains its authority and is still able to uphold the truth in maintaining its integrity and dignity. Because the judge's decision always contains instructions for the sake of justice based on the Almighty God and the decision must be accountable horizontally to the community and vertically to God Almighty. The research method used is normative legal research. This research is descriptive analytical. The data collection technique is done by means of literature study. The results of the study, namely the direction of supervision and guidance of judges that are relevant to actual problems related to the quality of judge decisions, will center on fostering a philosophical mindset, by introducing the philosophy of legal hermeneutics as a method for understanding texts and comprehensive facts, so that the quality of judge decisions always begins with a philosophical legal considerations that reflect the values ​​of philosophical justice contained in Pancasila. Because the judicial power is exercised based on the philosophy of Pancasila and the 1945 Constitution.